RELIVING MEMORIES (OVER AND OVER AGAIN): GIFS, MOVING PHOTOGRAPHY AND THE SMARTPHONE ALBUM - Kopelman, Sara; Frosh, Paul (AoIR Selected Papers of Internet Research, 2020)
This paper examines potential changes in the temporal experience of everyday digital media through the smartphone photo album. Smartphone photo albums not only organize and display domestic photographs but also initiate temporally novel photographic formats: for instance, the images taken by users can be used as raw material in the production of new kinds of ‘moving’ or ‘animated’ photographic products, usually formatted as GIF files and characterized by looped time. While the character of these products and the processes of their creation vary across operating systems, both Google’s and Apple’s systems radically disrupt the conventional assumptions of photography theory regarding photography’s relations with time. Pre-digital photography theory postulated a key distinction between a photograph and a movie or video: the photograph is static; the movie is characterized by temporal progression. In contrast, the GIF presents a shift from linear temporality to looped, cyclical time, promoting a present tense made visible not through instantaneous capture (photography) or sequential unfolding (film and video), but through continual recurrence. It eliminates the linearity of past-present-future because of its perpetual looped temporality, constituting a hybrid between photographic still and film or video. As a result, the repetitive movement of the GIF constructs a generalized impression of an event as an artificial duration without development, rather than the structured narrative of an event as a temporal unfolding. The emergence of the GIF in the smartphone album thus signals the rise of a new structure of memory and temporal experience in everyday mediated life.